Ajaran Kewikuan dalam Kidung Cowak: Menyusuri Konsep Spiritualitas Sekala dan Niskala - Juniawan, Ida Bagus Heri; Wiguna, Ida Bagus Alit Arta (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2024)
This study analyzes the concept of wiku in Kidung Cowak, a Balinese Hindu religious text that emphasizes the spiritual balance between sekala (material world) and niskala (spiritual world). In the Hindu traditions of Bali and Lombok, a wiku not only acts as a ritual leader, but also as a spiritual guide who directs people on the path of purity. This study uses a philological approach to inventory, translate and interpret the original manuscripts, as well as a hermeneutic approach to explore the symbolic meaning and relevance of Kidung Cowak's teachings in a modern context. The research findings show that Kidung Cowak views kewikuan as an ideal form of spiritual attainment, achieved through self-control, the practice of upawasa (fasting), yogic discipline, and a deep understanding of religious teachings or putusing aji. The text also provides guidance in choosing the right guru and criticizes wiku who focus on superficial aspects. The symbols in Kidung Cowak reveal a spiritual journey that demands harmony between social life and the ultimate spiritual goal of moksa. This study underscores the relevance of Kidung Cowak as a guide for wiku to achieve wisdom and inner peace amidst the challenges of modernization and globalization.